Indonesia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) report, supports the Government of Indonesia's efforts to reform the process of managing public resources, increase transparency in handling financial affairs, and combat corruption. The report assesses that the control environment in Indonesia is weak, despite a political leadership committed to improvement, and, recommends enacting a modern Budget Law, establish parliamentary public accounts, and audit committee, initiate reforms to develop a professional civil service, and, improve procurement laws, and practices in accordance with the Country Procurement Assessment. In addition, Budget execution, and monitoring remain weak, proposing to accelerate transition to a unified budget, improve policy review, by strengthening political inputs into budget preparation, and develop integrated revenue estimates within a macro framework. It emphasizes that the fragmentation in the accounting, and reporting of financial information does not produce reliable, and reconcilable sets of accounts, thus a rational financial management should be established, by creating the position of Accountant General within the Ministry of Finance, establishing financial controllership to handle financial planning, budgeting, and working capital management, and, improving treasury management. Finally, it is recommended that the current audit law be revised, by incorporating a public accounts committee, an independent auditor general, and, define their boundaries of responsibility.